PENGARUH KINERJA ESG TERHADAP KINERJA KEUANGAN PERUSAHAAN - Pramitya Khairunnisa, Dian; Erna Widiastuty (Jurnal Riset Akuntansi Aksioma, 2023)
This research aims to provide empirical evidence of the influence of environment, social, governance (ESG) performance on the financial performance of companies in Indonesia, Malaysia and Singapore. This research is quantitative research with secondary data from all public companies listed on the Indonesia Stock Exchange, Kuala Lumpur Stock Exchange and Singapore Stock Exchange in 2016-2021. Total observations in this study were 1.045 company-years. The independent variable of ESG performance is measured using the ESG score while the dependent variable of financial performance is proxied by ROA. This research using regression analysis on hypothesis testing. The results show that the influence of ESG on financial performance in Indonesia, Malaysia and Singapore varies. For example, in Indonesia and Malaysia the hypothesis which states that ESG has a positive and significant effect on financial performance is not supported. Meanwhile, in Singapore the hypothesis which states that the effect of positive and significant ESG on financial performance is supported. The results of testing each ESG component in each country show that the hypothesis is not supported because the direction is different from what was hypothesized.